ANALISIS PERAN KEPERCAYAAN, ULASAN, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN GOFOOD (STUDI KASUS DI KECAMATAN MEDAN PETISAH) - Melany, Livia; Tandhika, Maureen Mauretta; Tampubolon, Winny Gabyella; Nainggolan, Tuty (POLITEKNIK LP3I JAKARTA, 2026)
The development of digital technology has increased the use of food delivery services due to their practicality and efficiency. However, within the online food delivery industry in Indonesia, GoFood’s position has tended to weaken compared to GrabFood, which remains dominant, and ShopeeFood, which continues to grow. This decline in competitiveness is influenced by decreasing customer loyalty, driven by complaints such as delivery delays, lack of transparency in additional fees, and inconsistent promotions. Mismatches in discounts and free delivery offers have reduced trust, while negative reviews related to final pricing and fee systems have further worsened consumer perceptions. The population in this study includes all residents of Medan Petisah who use GoFood, the exact number of which is unknown or indefinite. Therefore, the sampling technique used is the Lemeshow formula, which allows the determination of sample size under conditions of an unknown population, resulting in a total of 96 samples. The sampling method applied is accidental sampling, where respondents are selected randomly based on their availability and willingness to participate in the study. Based on the research findings, it can be concluded that trust, reviews, and promotions each have an effect on customer loyalty toward GoFood in Medan Petisah District. Furthermore, these three variables simultaneously have a significant influence on customer loyalty.